2014
DOI: 10.1016/j.redox.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-based H2O2 signalling in microbial systems

Abstract: Cysteine residues, and in particular their thiolate groups, react not only with reactive oxygen species but also with electrophiles and with reactive nitrogen species. Thus, cysteine oxidation has often been linked to the toxic effects of some of these reactive molecules. However, thiol-based switches are common in protein sensors of antioxidant cascades, in both prokaryotic and eukaryotic organisms. We will describe here three redox sensors, the transcription factors OxyR, Yap1 and Pap1, which respond by disu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…This reacts with its target protein, Yap1, forming inter‐protein disulfide bonds, which then resolve to produce Yap1 with an intra‐protein disulfide. Yap1 disulfide enters the nucleus where it acts as a transcription factor (Boronat et al ., ). Plants have a wide range of TPXs in most subcellular compartments, and it has been suggested that these could act as H 2 O 2 sensors.…”
Section: H2o2 Signallingmentioning
confidence: 97%
“…This reacts with its target protein, Yap1, forming inter‐protein disulfide bonds, which then resolve to produce Yap1 with an intra‐protein disulfide. Yap1 disulfide enters the nucleus where it acts as a transcription factor (Boronat et al ., ). Plants have a wide range of TPXs in most subcellular compartments, and it has been suggested that these could act as H 2 O 2 sensors.…”
Section: H2o2 Signallingmentioning
confidence: 97%
“…Interestingly, overexpression or increased nuclear accumulation of Pap1 also confers the resistance on S. pombe to various other agents such as staurosporine [110], caffeine [111], and berefeldin A [112] and to DNA damage in checkpoint deficient mutants [113]. Scavenging the tyrosyl radical in RNR may also generate the hydroperoxy radical form of HU [17], which diffuses away and directly or indirectly modifies Yap1, leading to its accumulation inside the nucleus and transcriptional activation of genes involved in the redox response [106,114]. The activated Aft regulon promotes iron uptake, which may exacerbate the oxidative stress via Fenton reaction [19,115].…”
Section: Accumulation Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…In yeast, the classical system supporting this model is the hydrogen peroxide signaling pathway controlled by the TF Yap1 from S. cerevisiae [248][249][250]. Yap1 is a basic leucine zipper (bZIP) TF that responds to hydrogen peroxide by activating the expression of genes for antioxidant enzymes and components of thiol homeostasis [251,258].…”
Section: Thiol-disulfide Exchange In Yeast Redox-sensing Transcriptiomentioning
confidence: 99%
“…Consequently, the Yap1-Crm1 complex is disrupted and Yap1 accumulates in the nucleus, leading to the activation of target genes (reviewed in Ref. [248]). Both Gpx3 and Yap1 are specifically reduced by the thioredoxin system upon removal of the stress, restoring the localization of Yap1 in the cytoplasm [249,253].…”
Section: Thiol-disulfide Exchange In Yeast Redox-sensing Transcriptiomentioning
confidence: 99%